THE EFFECT OF AEROBIC EXERCISE TO THE WEIGHT REDUCTION OF CIVIL SERVANTS WHICH HAVE OVERWEIGHT IN THE EDUCATION OFFICE OF NORTH SUMATERA - Sabar Surbakti; Dika Nella (Universitas Negeri Medan, 2019)
The purpose of this study was to determine whether there was an effect of aerobic exercise on weight loss of Civil Servants who are overweight in the Education Office of North Sumatra. This study used an experimental method which was giving treatment to the sample. The treatment given was in the form of aerobic exercise where the study was lasted for 6 weeks. This study used a pre-test and post-test one group design research design. The population in this study was the State Civil Apparatus in the Education Office of North Sumatra, the PMPTK (Development of Education Quality and Education Personnel Quality) totaling 30 people, 16 women and 14 min, then the research sample was determined by means of a proportional sampling which was sampling using some criteria. Based on these criteria a sample of 10 people was obtained. To test the hypothesis needed research data was obtained through research instruments. The instrument / research used a weight and height scale, the data analysis technique used the t-test statistic with a significance level of 0.05. From the results of the analysis data obtained weight loss with an average of 3.58 with a t-value of 13.6 > at Db 9 with a confidence level of 0.05 t-table value was 1.83. T-count t-table (13,671,83), then Ho was rejected and Ha was accepted. Then it was concluded that aerobic exercise gave a significant effect on weight loss in the State Civil Apparatus which was overweight in the Education Office of North Sumatra.